Exploration of Climate Change on Mental Health in Indonesia: Systematic Analysis Review - Alfrisa Renuat; Muhammad Arkan Muhadzib; Depy Eka Rachmawati (Proceeding International Conference Restructuring and Transforming Law, 2024)
Currently, the world is facing a serious challenge in the form of climate change. Climate change gives rise to more devastating weather anomalies and natural disasters. The impact can be felt directly through physical and indirect damage felt by humans, one of which is mental health problems. Climate change also poses a threat to sustainable development in Indonesia. In the 2021 Climate Transparency report , it is reported that Indonesia's climate is in the " highly insufficient " category or so inadequate in reducing greenhouse gas emissions that it is estimated that by 2030-2050, climate change will cause additional deaths per year of ¼ million people due to malnutrition (lack of nutrition). ), malaria, heat wave stress. This literature review aims to review existing journals regarding the relationship between climate change and mental health, as well as what methods have been used to deal with it. The research method used is a systematic analysis review. The results we found were that there is still little Indonesian literature that discusses the impact of climate change on mental health and that climate change in Indonesia has the opportunity to impact individual mental health.